Association Between Hospital Volume and Failure to Rescue After Open or Endovascular Repair of Intact Abdominal Aortic Aneurysms in the VASCUNET and International Consortium of Vascular Registries. Issue 5 (November 2021) - D'Oria, Mario; Scali, Salvatore; Mao, Jialin; Szeberin, Zoltán; Thomson, Ian; Beiles, Barry; Stone, David; Sedrakyan, Art; Eldrup, Nikolaj; Venermo, Maarit; Cassar, Kevin; Altreuther, Martin; et al.
Abstract : Objective: To investigate the association between hospital volume and failure to rescue (FtR), after open repair (OAR), and endovascular repair (EVAR) of intact abdominal aortic aneurysms (AAA) among centers participating in the VASCUNET and International Consortium of Vascular Registries. Summary of Background Data: FtR (ie, in-hospital death following major complications) is a composite end-point representing the inability to treat complications effectively and prevent death. Methods: Using data from 8 vascular registries, complication and mortality rates after intact AAA repair were examined (n = 60, 273; EVAR-43, 668; OAR-16, 605). A restricted analysis using pooled data from 4 countries (Australia, Hungary, New Zealand, and USA) reporting data on all postoperative complications (bleeding, stroke, cardiac, respiratory, renal, colonic ischemia) was performed to identify risk-adjusted association between hospital volume and FtR. Results: The most frequently reported complications were cardiac (EVAR-3.0%, OAR-8.9%) and respiratory (EVAR-1.0%, OAR-5.7%). In adjusted analysis, 4.3% of EVARs and 18.5% of OARs had at least 1 complication. The overall FtR rate was 10.3% after EVAR and 15.7% after OAR. Subjects treated in the highest volume centers (Q4) had 46% and 80% lower odds of FtR after EVAR (OR = 0.54; 95% CI = 0.34–0.87; P = 0.04) and OAR (OR = 0.22; 95% CI = 0.11–0.44; P < 0.001) when compared to lowest volume centers (Q1), respectively. Colonic ischemia had the highest risk of FtR for both procedures (adjusted predicted risks, EVAR: 27%, 95% CI 14%–45%; OAR: 30%, 95% CI 17%–46%). Conclusions: In this multi-national dataset, FtR rate after intact AAA repair with EVAR and OAR is significantly associated with hospital volume. Hospitals in the top volume quartiles achieve the lowest mortality after a complication has occurred. Abstract : Supplemental Digital Content is available in the text